Stopping power of Hetero nuclear di-cluster ions from partial-wave analysis based on semi classical phase shifts - Salman, Nadher A.; Ahmed, Khalid A.; Ahmed, Baida M. (Iraqi Journal of Science, 2022)
We apply a semi classical partial-wave scattering method based on the induced density approach (IDA) model. For ion electron scattering, the transport cross section is used to calculate the energy loss. This method yields a non-perturbative exemplification of energy loss, bridging the difference among classical and quantal representations. The focus of this work is the interaction of hetero nuclear di-cluster (He-H) ions with a free gas. The results show three kinds of stopping power in (a.u) (cluster stopping power, self-stopping power and correlated stopping power) of hetero nuclear di-cluster ions (He-H) with velocity at different atomic di-cluster distances at different densities and temperatures. We find that Bragg’s peak of stopping power is directly proportional to density and temperatures and inversely with atomic di-cluster distance . The equations in present work are programmed in fortran-90 for numerical calculations.